2015
DOI: 10.1080/17542863.2015.1103276
|View full text |Cite
|
Sign up to set email alerts
|

The association between duration of untreated psychosis in first psychotic episode patients and help seeking behaviors in Jogjakarta, Indonesia

Abstract: Help seeking is predictor of prognosis in the first episode of psychotic disorders. Caregivers play a key role in deciding from whom to seek help. In Indonesia, caregivers often seek help from alternative healers first and health professionals later, which is believed to result in delayed psychiatric treatment and risk for poor prognosis. This study measured the duration of untreated psychosis (DUP) in a sample of 100 persons being treated for a first episode of psychosis in Yogyakarta, Indonesia. We attempted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…Fifty-six peer-reviewed articles were found from 1987 to 2017 [21][22][23], and 19 articles from Indonesian journals from 2001 to 2016 [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96]. Looking at the publication dates, health-seeking behavior in Indonesia drew little attention before 2000, with only six articles before that time.…”
Section: Description Of Relevant Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-six peer-reviewed articles were found from 1987 to 2017 [21][22][23], and 19 articles from Indonesian journals from 2001 to 2016 [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96]. Looking at the publication dates, health-seeking behavior in Indonesia drew little attention before 2000, with only six articles before that time.…”
Section: Description Of Relevant Literaturementioning
confidence: 99%
“…Indonesian people's choice of health providers is determined by complex and interrelated factors: sociodemographic characteristics, influence of significant others, sociocultural beliefs, perception about diseases and their causality, and perception of medical services including accessibility and availability, particularly in rural and areas, and its related cost [23,[28][29][30]34,35,38,[40][41][42][45][46][47][48]52,[54][55][56][57]59,60,64,65,67,72].…”
Section: Determinants Of Health Provider Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Javanese families often play a significant role in the management of patients with psychotic disorders, our previous studies have shown that they hold different explanatory models for the disorders and for recovery than those of health practitioners (Good & Subandi, 2004;Marchira, Puspitasari, Mulyani, & Rochmawati, 2016;Marchira, Supriyanto, Subandi, & Good, 2016). Discrepancies in understanding of illness and treatment between caregivers and health practitioners have been shown in many studies (Jorm, Angermeyer, & Katschnig, 2000;Riedel-Heller, Matschinger, & Angermeyer, 2005;Wright, Harris, Wiggers, & Jorm, 2005).…”
mentioning
confidence: 99%
“…Dr Good's book, edited with psychiatrist Devon Hinton, Panic Disorders (2009) is a landmark in the study of that (or those) condition (88). As well, we note that rather than prejudging a condition, thus westernizing it, he, and DelVecchio Good have studied undefined ''psychoses'' or ''madness'' rather than 'schizophrenia' (e.g., 83,90,92,94,116,120). A recent work, Culture and PTSD, also edited with Devon Hinton, considers issues taken up earlier, the facts of violence and trauma and their influence on daily life and on forms of affliction in specific contexts (113,114,118).…”
Section: Publicationsmentioning
confidence: 96%